The use of Facebook in the Slovenian local self-government - Jukić, Tina (Central European Public Administration Review, 2018)
The paper presents a contribution to the rapidly growing field of social networks usage in public administration organizations. Despite the increasing volume of research in this field, there is a lack of detailed empirical evidence. To address the issue, we aim here at comprehensive empirical analysis of the usage of Facebook as the most popular social networking site among Slovenian municipalities. The methodology of research is based on 21 indicators measuring usage, engagement, multichannel features, multi-media content, and the existence of a social networks usage strategy. The measurement has been performed in each of the 212 Slovenian municipalities. Their Facebook interaction has been observed in a period of six months, from November 2015 to May 2016. The analysis results reveal that only 36% of the Slovenian municipalities were present on Facebook in 2016, with almost a quarter having a zero interaction rate on their Facebook pages/profiles in the observed six-month period. In particular, one-way interaction was recorded on municipal Facebook pages, leaving considerable room for improvement as regards the usage of Facebook as a social network with the highest potential of reach and engagement in terms of number of its users. The results are useful for information and benchmarking purposes for Slovenian and foreign municipal managers.
Keywords: družbena omrežja; državljani; e-participacija; e-uprava; Facebook; lokalna samouprava; občine; participacija; Slovenija; socialne mreže; socialni mediji; sodelovanje državljanov